Blueschist from the Mariana forearc records long-lived residence of material in the subduction channel - Tamblyn, Renee; Schmitt, Axel Karl (Earth and planetary science letters, 2019)
From ca. 50 Ma to present, the western Pacific plate has been subducting under the Philippine Sea plate, forming the oceanic Izu-Bonin-Mariana (IBM) subduction system. It is the only known location where subduction zone products are presently being transported to the surface by serpentinite-mud volcanoes. A large serpentine mud “volcano” forms the South Chamorro Seamount and was successfully drilled by ODP during Leg 195. This returned mostly partially serpentinized harzburgites enclosed in serpentinite muds. In addition, limited numbers of small (1 mm-1 cm) fragments of rare blueschists were also discovered. U-Pb dating of zircon and rutile from one of these blueschist clasts give ages of 51.1 ± 1.2 Ma and 47.5 ± 2.0 Ma, respectively. These are interpreted to date prograde high-pressure metamorphism. Mineral equilibria modelling of the blueschist clast suggests the mineral assemblage formed at conditions of ∼1.6 GPa and ∼590°C. We interpret that this high-pressure assemblage formed at a depth of ∼50 km within the subduction channel and was subsequently exhumed and entrained into the South Chamorro serpentinite volcano system at depths of ∼27 km. Consequently, we propose that the material erupted from the South Chamarro Seamount may be sampling far greater depths within the Mariana subduction system than previously thought. The apparent thermal gradient implied by the pressure-temperature modelling (∼370°C/GPa) is slightly warmer than that predicted by typical subduction channel numerical models and other blueschists worldwide. The age of the blueschist suggests it formed during the arc initiation stages of the proto-Izu-Bonin-Mariana arc, with the P-T conditions recording thermally elevated conditions during initial stages of western Pacific plate subduction. This indicates the blueschist had prolonged residence time in the stable forearc as the system underwent east-directed rollback. The Mariana blueschist shows that subduction products can remain entrained in subduction channels for many millions of years prior to exhumation.
Gesehen am 16.07.2019